Effect of Organic Matters And Water Stress On Performance of Rice in Vegetative Phase - Cut Nur Ichsan; Erida Nurahmi; Oktrya Rochmad; Bakhtiar Bakhtiar; Efendi Efendi; Sabaruddin Sabaruddin (Syiah Kuala University, 2015)
Drought become a major limiting factor in world cereal production. Various methods are used to solve this problem such as irrigation management by managing the soil moisture effectively for the plants to grow normally. Another way to improve the water holding capacity with the addition of organic matter in soil. Another way by planting drought tolerant rice varieties. Drought-tolerant rice varieties like Inpago 8 with various doses of organic matter and water stress at vegetative phase treatment done to analyze the change of rice plant performance at the vegetative phase of the rice crop due to drought and organic matter dose. At very low water content, which happened repeatedly during the vegetative phase causes the change in root growth, plant height, length and width of rice leaf significantly